Pulmonary complications requiring surgical intervention caused by endometriosis – case studies - Kamila Stopińska; Mariusz Kazimierz Wójtowicz; Karolina Marczak; Olga Grzelak (Journal of Pre-Clinical and Clinical Research, 2022)
Endometriosis is a condition described as growth of the endometrium outside the uterine cavity. Lesions can occur in many areas of the body, including the pleural cavity and lungs. Etiology of this condition is still unknown. Two medical cases are described: a 47-year-old patient reporting chest pain, who had resection of the apex of the right lung a year earlier,and 41-year-old patient with frequent lower abdominal pain and recurrent haemoptysis for about 16 years, which had been the cause of multiple hospitalizations in pulmonary departments. Both patients underwent several examinations – tomography, MRI, and surgical diagnostics. In both cases, the tests showed the presence of thoracic endometriosis. The described cases indicate diagnostic and therapeutic difficulties in patients with thoracic endometriosis. In conclusion, treatment of the manifestation of thoracic endometriosis is a great challenge because of limitation of the possibilities for surgical procedures and non-invasive diagnostic tests.